Adoption of National Identity in Metropolises: A Study in Istanbul - Ece Doruk; Seda Mengü (Selçuk İletişim)
National identity is the formation a common consciousness and language through the establishment of a common background, national ideology, ethics, emotions, remembrance and traditions in all individuals of a nation. Accordingly, having a rich historical background refers to the volition to live together as well as protect common values. Ethnic backgrounds of societies as well as their production and consumption practices, languages, religions, artistic concepts and development of similar elements throughout history also contributes to the formation of national culture concept in minds. Identity is expressed with several symbols denoting particular differences with regard to the others. Conceptualization of identity pertains to the categorizations of social relations into two groups (we and others) at least. With regard to all these, the purpose of our study is to depict the profile of the existence of national identity depending on economic, cultural and social changes, which has been created by modernity in different local areas of metropolises. Meanwhile, the characteristics of different local areas adopting national identity strongly or weakly, or not assuming it at all as well as the factors, which bring about such an adoption, will be studied. Therefore, 257 people living in different areas of Istanbul will be given questionnaires. Considering development levels, socio-economic status, population densities of different districts, a research field will be formed with random sampling method. Questionnaires will be implemented through interviews with individuals. Following the completion of field research, questionnaires will be evaluated with computer and the findings will be reported accordingly.